2008
DOI: 10.1007/s10834-008-9112-0
|View full text |Cite
|
Sign up to set email alerts
|

The Labor Market Participation of Sandwich Generation Italian Women

Abstract: We empirically analyzed the labor market participation of Italian women, with special emphasis on the role of intergenerational family links. Older relatives, on the one hand, discourage the work participation of women by requiring care; on the other hand they may provide household services favoring labor supply. We studied this dual impact estimating a trivariate probit model where the three choices to be in the labor force, to use informal help from older relatives and to care for them are jointly determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 26 publications
1
39
0
2
Order By: Relevance
“…A related branch of study examines the importance of time transfers from grandparents. They consistently find that grandparent support in grandchild care and household chores effectively promotes the labor supply of married women (Arpino, Pronzato, and Tavares 2014;Del Boca 2002;Wolff 2008, 2011;Pagani and Marenzi 2008;Posadas and Vidal-Fernandez 2013;Zamarro 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A related branch of study examines the importance of time transfers from grandparents. They consistently find that grandparent support in grandchild care and household chores effectively promotes the labor supply of married women (Arpino, Pronzato, and Tavares 2014;Del Boca 2002;Wolff 2008, 2011;Pagani and Marenzi 2008;Posadas and Vidal-Fernandez 2013;Zamarro 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, the share of independent-living elders rose sharply from 26.7% to 41.7% over the same period (Hu and Peng 2014). 6 Given the frequent time and monetary transfers in multi-generational households, researchers have increasingly paid attention to the impact of coresidence with elderly parents on female labor supply in Japan (Ogawa and Ermisch 1996;Sasaki 2002), South Korea (Chun, Kim, and Lee 2009), the United States (Kolodinsky and Shirey 2000;Compton and Pollak 2014) and Europe (Pagani and Marenzi 2008). The few articles touching upon the subject in China have revealed that grandparents in multi-generational households undertake a tremendous amount of grandchild care, which significantly reduces a mother's involvement in childcare (Chen, Liu, and Mair 2011;Chen, Short, and Entwisle 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most important change female employment entails is a shift in the gender balance in households and societies, as the traditional breadwinner model is rapidly disappearing in Western countries (McDonald 2000). The rise in female employment is also vitally important for the sustainability of social protection systems, especially in the context of rapid population ageing (Pagani and Marenzi 2008). There is consequently considerable interest in understanding the role of female labour force participation in Western societies.…”
Section: Introductionmentioning
confidence: 99%
“…too centered on the role of women as the main care givers for both children and the elderly (Villa andBettio 1998, Pagani andMarenzi, 2008), or the lack of flexible work arrangements capable of reconciling family and market work such as part-time employment opportunities (Del Boca, 2002). Thus, also from a policy point of view, it is interesting to understand whether "tempo policies" (Lutz and Skirbekk 2005), i.e.…”
mentioning
confidence: 99%